Antagonistic Ability and Fungicide Tolerance of Actinomycetes from the Rhizosphere of Maize (Zea mays L.) Plants in Gorontalo - Danial Mohamad; Yuliana Retnowati; Novri Youla Kandowangko; Abubakar Sidik Katili; Wirnangsi Din Uno (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Actinomycetes are a group of microbes that live in the rhizosphere of plants and play an important role in soil microbial dynamics. This study aims to describe the antagonistic ability against pathogenic molds and tolerance to fungicides in actinomycetes from the rhizosphere of maize plants in Gorontalo. This research is descriptive uses a quantitative approach and employs a purposive sampling technique. Rhizosphere soil samples were collected from maize fields in the hilly area of Bontula Village, Asparaga District, Gorontalo Regency. The results showed the presence of 7 actinomycetes isolates with different morphological characteristics, namely RFZm-PG, RFZm-PLG, RFZm-PW, RFZm-PB, RFZm-PR, RFZm-PY, and RFZm-PO. Antagonistic tests showed that four isolates (RFZm-PB, RFZm-PG, RFZm-PLG, RFZm-PW) inhibited the growth of Fusarium oxysporum and Neocosmospora solani with an inhibition percentages of 66.38%-89%. The fungicide tolerance test showed that the seven isolates were tolerant to thiram, dimethomorph and benomyl, with the highest inhibitory effect by thiram. Isolates RFZm-PG and RFZm-PLG had the highest tolerance up to 500 ppm, while other isolates were tolerant only up to 400 ppm. Molecular analysis showed that RFZm-PG belongs to the genus Streptomyces (100% similarity with Streptomyces enissocaesilis), while RFZm-PLG belongs to Nocardiopsis (100% similarity with Nocardiopsis synnemataformans).